Arithmetic-Analytic Representation of Peano Curve - Guangjun Yang; Xiaoling Yang; Ping Wang (International Journal of Mathematics and Mathematical Sciences)
In this work, we obtained a nonmatrix analytic expression for the generator of the Peano curve. Applying the iteration method of fractal, we established a simple arithmetic-analytic representation of the Peano curve as a function of ternary numbers. We proved that the curve passes each point in a unit square and that the coordinate functions satisfy a Hölder inequality with index α=1/2, which implies that the curve is everywhere continuous and nowhere differentiable.